The repopulation of New Orleans after Hurricane Katrina - McCarthy, Kevin F., 1945- (Technical report (Rand Corporation), 2006)
In November 2005, New Orleans city leaders asked RAND to estimate the repopulation of the city in the aftermath of Hurricane Katrina. The Bring New Orleans Back Commission needed estimates of the city b2 ss population in the immediate future (the next three to six months) and the near-term future (the next one to three years) to guide the redevelopment planning process. The study was completed in early January 2006. A conceptual framework based on the costs and benefits of migration and on the role of social networks and physical constraints guided the estimates. Housing habitability was determined to be the key driver of the future population of New Orleans. RAND developed an approach to estimating future population for four points in time based on estimates of housing habitability, which were, in turn, determined by floodwater depth and the pace of housing reconstruction, as well as an estimate of the pre-Katrina population by the condition of its housing after Katrina. An important role for policymakers in shaping the repopulation process in New Orleans will be to minimize the uncertainty faced by residents and businesses by speeding up the reconstruction process.